PENANAMAN SIKAP NASIONALISME MELALUI PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Riyanti, Wiwin; Rachman, Maula Aulia; Handayani, Tulus (DIRASATUL IBTIDAIYAH, 2023)
This research aims to determine the forms, methods and factors in cultivating nationalist attitudes. This research uses qualitative research with a literature study approach. Data collection is carried out by determining the topic, collecting various data sources and drawing conclusions. The results of the research show that the way teachers instill an attitude of nationalism through social studies learning includes habituation, exemplary activities, the use of stories and media. Forms of cultivating an attitude of nationalism include being proud of being Indonesian, loving the country, being willing to make sacrifices, respecting culture, respecting the services of heroes and prioritizing the public interest. The causes of obstacles to cultivating a nationalist attitude are limited facilities and infrastructure, time, and students' lack of understanding. Keyword: Attitudes; Nationalism; Students.